REPRESENTATION OF THE ESPRESSO AS POPULAR CULTURE IN MALANG - HAKIM, MOH LUTFI (Jurnal Ilmiah Mahasiswa FIB, 2014)
Lutfi Hakim, Mohammad. Representation of the Espresso as Popular Culture in Malang. Study Program of English, Department of Languages and Literature, Faculty of Cultural Studies, Universitas Brawijaya.Supervisor: Scarletina Vidyayani Eka; Co-supervisor: Aris Siswanti.Keywords: Espresso, Popular Culture, Representation, ConstructionistThis study focused on Malang Coffee Houses using the Espresso machine. This study aimed at discovering  the relation on  (1) How the capital owners with their strategies, knowledge/power, technologies, and apparatuses (Barista) change the perspective of society to consume Espresso  (2)  How the implication of Espresso by the society becoming a form of new culture in Malang. Popular culture is  a product  of  culture  itself  which  is appealing new culture. Espresso popularity is marked with the propagation of Coffee houses that use Espresso machines. The representation of Espresso includes things, concepts, and signs.  Furthermore, this study uses Constructionist  approach  referred  to the social practices  constructing  feedback  toward espresso culture.  This study used ethnomethodology  including participant and non-participant observation  through (1) documentation, (2) surveys, and (3) interview conducted in 8oz Coffee Studio, Golden Heritage Koffie, and Coffee Story Malang. This study found out  that the Informant (the apparatus) and the Respondent (customer or society) constructed the same implication of Espresso. Apparatus as the constructor  of Espresso popularity  constructed  the society mindset that Espresso is part of modern society to replace conventional coffee. This mindset is not in a certain social class only, but also in all of social classes which finally like to consume Espresso. Representation of Espresso can be stated as popular culture.